BEBERAPA FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA PADA UMKM BAKSO BAKAR SS KOTA MALANG - Jatmiko Setiaji; Rizki Aprilia Dwi Susanti; Cakti Indra Gunawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study was made to investigate what factors can have an impact on work productivity. The investigation here focuses on knowing whether there is an effect of the variables of work facilities, compensation and welfare on the work productivity of employees, both productivity in certain aspects and overall. This research was conducted at MSME Bakso Bakar SS Malang City which has 30 employees. The type of approach that will be applied in the research is the quantitative method and saturated sampling of all MSME employees without exception will be involved as the research sample. From the data that has been further processed, it shows that the provision of compensation does not have a significant impact on increasing employee productivity as evidenced by the t arithmetic value which is smaller than t table and the significant probability value parameter obtained above 0.05. The variables that actually have a more significant effect on the work productivity of employees are supporting facilities and welfare insurance. This is proven by the value of calculated f which is higher than f table and the significance probability value is below 0.05.